ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI REPURCHASE INTENTION KONSUMEN PADA SITUS JUAL BELI ONLINE LAZADA.CO.ID - Dio Ananta Putra; Verinita Verinita (Ekonis: Jurnal Ekonomi dan Bisnis, 2020)
Along with the times and technology, internet usage in the world today continues to increase. The rapid development of internet users in this era of globalization has led to changes in culture in human life. The e-commerce phenomenon that began to grow rapidly in Indonesia is an online trading site. One of the online trading sites that are developing in Indonesia today is lazada.co.id. In buying and selling sites that affect success and profitability are consumer repurchase intentions. This study discusses the analysis of factors that influence consumers' repurchase intention on the online trading site lazada.co.id. The sample of this research is 170 consumers who have shopped more than once on the online trading site Lazada.co.id and are more than 17 years old, who already have the ability to make their own decisions and live in Padang City. The research design used is quantitative with explanatory type. This research will use Partial Least Square (PLS) analysis method, while the variables used are the factors that influence consumers' repurchase intention on online buying and selling sites. The relationship between the factors that influence consumer interest and the repurchase decision made by online trading site consumers in Padang City is obtained. Keyword: Repurchase intention, Costumer